Epizooic metazoan meiobenthos associated with tubeworm and mussel aggregations from cold seeps of the northern Gulf of Mexico - Bright, M. (Pergamon Press, 2010)
The abundance and higher taxonomic composition of epizooic metazoan meiobenthic communities associated with mussel and tubeworm aggregations of hydrocarbon seeps at Green Canyon, Atwater Valley, and Alaminos Canyon in depths between 1400 and 2800 m were studied and compared to the infaunal community of non-seep sediments nearby. Epizooic meiofaunal abundances of associated meiobenthos living in tubeworm bushes and mussel beds at seeps were extremely low (usually <100 ind. 10 cm(−2)), similar to epizooic meiofauna at deep-sea hydrothermal vents, and the communities were composed primarily of nematodes, copepods, ostracods, and halacarids. In contrast, epizooic meiobenthic abundance is lower than previous studies have reported for infauna from seep sediments. Interestingly, non-seep sediments contained higher abundances and higher taxonomic diversity than epizooic seep communities, although in situ primary production is restricted to seeps.